Bacterial translocation in rats nonfunctioning diverted distal colon - Pinto Júnior,Francisco Edilson Leite (2007)
PURPOSE: To investigate whether the alterations of the diverted colon segment mucosa, evidenced in fecal colitis, would be able to alter Bacterial Translocation (BT). METHODS: Sixty-two Wistar male rats ranging from 220 to 320 grams of weight, were divided in two groups: A (Colostomy) and B (Control), with 31 animals each one. In group A, all animals underwent end colostomy, one stoma, in ascending colon; and in the 70th POD was injected in five rats, by rectal route diverted segment - 2ml of a 0.9% saline solution in animals (A1 subgroup); in eight it was inoculated, by rectal route, 2ml of a solution containing Escherichia coli ATCC 25922 (American Type Culture Collection), in a concentration of 10(8) Colony Forming Unit for milliliters (CFU/ml) - A2 Subgroup; in ten animals the same solution of E. coli was inoculated, in a concentration of 10(11) CFU/ml (A3 Subgroup); and in eight it was collected part of the mucus found in the diverted distal colonic segment for neutral sugars and total proteins dosage (A4 subgroup). The animals from the group B underwent the same procedures of group A, but with differences in the colostomy confection. In rats from subgroups A1, A2, A3, B1, B2, and B3 2ml of blood were aspirated from the heart, and fragments from mesenteric lymphatic nodule, liver, spleen, lung and kidney taken for microbiological analysis, after their death. This analysis consisted of evidencing the presence of E. coli ATCC 25922 CFU. Mann-Whitney and ANOVA Tests were applied as analytic techniques for association of variables. RESULTS: The occurrence of BT was evidenced only in those animals in which inoculated concentration of E. coli ATCC 25922, reached levels of 10(11)CFU/ml, i.e. in Subgroups A3 and B3, although, being significantly greater (80%) in those animals without colostomy (subgroup B3) when compared to the ones with colostomy (20%) from the subgroup A3 (P <0.05). Lung, liver and mesenteric lymphatic nodules were the tissues with larger percentile of bacterial recovery, so much in subgroup A3, as in B3. Blood culture was considered positive in 60% of the animals from subgroup B3 and in 10% of those from subgroup A3 (p <0.05). There was greater concentration of neutral sugars, in subgroup A4 - mean 27.3mg/ml -, than in subgroup B4 - mean 8.4mg/ml - (P <0.05). CONCLUSION: The modifications in the architecture of intestinal mucosa in colitis following fecal diversion can cause alterations in the intestinal barrier, but it does not necessarily lead to an increased frequency of BT.